Effect of vitamin D levels in benign paroxysmal positional vertigo - Sawant, Shweta; Nandini, Taranath; Partabad, Rajashree (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Benign paroxysmal positional vertigo (BPPV) is a common cause of disabling vertigo with a high rate of recurrence. BPPV is the most common cause of neurotological disorder. It is caused by dislodged otoconia which fall from the utricular macula and float into the semicircular canals there by making them sensitive to gravity. It has been shown that elderly people may suffer from unrecognized, chronic BPPV. Patients with unrecognized BPPV were more likely to have reduced activity of daily living scores, to have sustained a fall in the previous 3 months and to have depression. Methods: A prospective study of 100 patients with clinical diagnosis of BPPV visiting Navodaya medical college and hospital between June 2019 to May 2020 were included in the study. Results: Patients taking both vitamin D supplementation and rehabilitation therapy improved better than patients taking rehabilitation therapy alone. Conclusions: Both rehabilitation therapy and supplementation of vitamin D is helpful in patients with vitamin D deficient BPPV patients.